Limited recovery following a massive seagrass decline in subarctic eastern Canada. Issue 2 (2nd November 2022) - Leblanc, Mélanie‐Louise; O'Connor, Mary I.; Kuzyk, Zou Zou A.; Noisette, Fanny; Davis, Kaleigh E.; Rabbitskin, Ernie; Sam, Laura‐Lee; Neumeier, Urs; Costanzo, Rémi; Ehn, Jens K.; Babb, David; Idrobo, C. Julián; et al.
Abstract: Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover (<25%), low aboveground biomass, smaller shoots than before 1995, and marginally low densities persisted at most sites. Overall, the synthesized datasets show a 40% loss of eelgrass meadows with >50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming. Abstract : In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated to respond to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. Overall, the 40% loss of eelgrass meadows with >50% cover in eastern James Bay since 1995 demonstrated from the synthesized data sets represents the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. The results caution against assuming subarctic seagrass ecosystems will benefit from ongoing climate warming.